Sepsis therapies: learning from 30 years of failure of translational research to propose new leads. Issue 4 (16th March 2020) - Cavaillon, Jean‐Marc; Singer, Mervyn; Skirecki, Tomasz
Abstract: Sepsis has been identified by the World Health Organization (WHO) as a global health priority. There has been a tremendous effort to decipher underlying mechanisms responsible for organ failure and death, and to develop new treatments. Despite saving thousands of animals over the last three decades in multiple preclinical studies, no new effective drug has emerged that has clearly improved patient outcomes. In the present review, we analyze the reasons for this failure, focusing on the inclusion of inappropriate patients and the use of irrelevant animal models. We advocate against repeating the same mistakes and propose changes to the research paradigm. We discuss the long‐term consequences of surviving sepsis and, finally, list some putative approaches—both old and new—that could help save lives and improve survivorship. Abstract : This review recapitulates our knowledge on sepsis and its long‐term consequences, the lack of therapeutic advances in the last decades, and proposes new approaches to improve sepsis survival.